Influence of the Social Media on Choosing the Destination - Marković, Ivana; Rabasović, Biljana; Janković Perić, Marina (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Social media is playing an increasingly important role in many aspects of tourism. While planning a trip, tourists look for information on social media, consider the comments of users who have already visited the destination, and share their experiences about the destination during and after the holiday. Therefore, social media has been proven as an excellent channel for promotion and communication with tourists, as well as an effective complaint management system. This topic has been the subject of many studies that explored the role of social media in promoting, building the image and brand of a tourist destination, while few studies have explored the impact of social media on tourist destination choice. Therefore, the subject of this paper is to analyze the influence of social media on choosing the tourist destination. The aim of this paper is to examine the impact of the availability of information related to the destination and user-generated content through social media on the tourist destination choice. Data were collected using the online survey technique, and research hypotheses were tested by regression analysis. The study results indicated the importance of the availability of information about the destination and a word-of-mouth propaganda on social media while choosing a destination. The theoretical contribution is reflected in new information regarding the role of social media in tourism, which is limited in the domestic scientific literature. As a practical contribution, the study provides information that may be useful to tourism service providers in creating a promotional campaign on the Internet.